2015
DOI: 10.5114/ceji.2015.52830
|View full text |Cite
|
Sign up to set email alerts
|

Clinical immunology Recurrent respiratory tract infections in children – analysis of immunological examinations

Abstract: BackgroundPaediatric respiratory tract infections are among the most common reasons for preschool and school absences and visits to physicians. The disease mainly involves the upper respiratory tract and is associated with fever, cough, sore throat, and running nose. Children with recurrent respiratory infections (RRI), which are defined as more than six serious diseases a year, are a difficult diagnostic challenge. The aim of this study was to assess immunological deviations in laboratory tests performed in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Recurrent RTIs (RRTIs) often prolong the recovery period, increase the required health care, and cause more frequent complications, such as autoimmune disorders and septicemia [2]. Previous studies showed that the incidence of RRTIs among children in northern China ranged from 17.8% to 18.7% in 2011 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent RTIs (RRTIs) often prolong the recovery period, increase the required health care, and cause more frequent complications, such as autoimmune disorders and septicemia [2]. Previous studies showed that the incidence of RRTIs among children in northern China ranged from 17.8% to 18.7% in 2011 [3].…”
Section: Introductionmentioning
confidence: 99%
“…A well‐designed review concluded that YPFF improved the immune function through acting on immune organs, non‐specific immunity and specific immunity (Zhou et al, ).Together these findings implied anti‐infective effects of YPFF may be correlated to its immunomodulating effect. However, there is no consensus on the immunoglobulin levels or T‐lymphocytes count and recurrence or improvement of symptoms in children with RRTIs (Esposito and Musio, ; Raniszewska et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Children with primary immunodeficiency often present a higher susceptibility to RRTIs. However, most of children diagnosed with RRTIs did not exhibit an immunodeficiency, and only a small part of patients showed mild decrease in serum levels of IgA or IgG and ratio of CD4 + /CD8 + (Finocchi et al, ; Han et al, ; Kendirli et al, ; Qu and Dong, ; Raniszewska et al, ). RRTIs are usually treated with immunomodulating agents (Chen and Zhao, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent respiratory infections are defined as >6 respiratory infections in 1 year . Patients with an HAZ below ‐2 were referred to the pediatric endocrinology outpatient clinic for GH deficiency.…”
Section: Methodsmentioning
confidence: 99%